(untitled) (Research, Society and Development, 2022)
The industrial process is the main cause of generation of by-products, highlighting the food industry that uses tons of fruits that are discarded, these are great sources of active compounds with recycling potential. The objective of this work was to search for studies with the residues of the food industry and to identify alternatives to reduce the loss. This is a review which was developed from the analysis of studies found in 2 databases: PubMed and Google Scholar. Works were selected that involved plant species associated with food waste and possible alternatives to minimize the environmental impact. The species Citrus sinensis, Persea americana, Musa spp., Punica granatum and Hylocereus undatus presented alternatives to combat waste and present biological activity. The use of unconventional parts of fruit is a sustainability practice, leading to less disposal of organic waste to the environment, consequently reducing the negative impact.